INTERPRETASI SEPUTAR MITOS MEMPENGARUHI MENTALITAS MASYARAKAT KOTA PALU DI AWAL MASA PANDEMI COVID 19 - Jefrianto Jefrianto (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2022)
Myths about how to protect yourself from COVID-19 affected the mentality of the people of Palu City at the start of the pandemic. When the first case of COVID-19 appeared in Palu City on March 26, 2020, various myths about how to protect yourself from COVID-19 emerged. How do the myths about this pandemic quickly affect the mentality of the people of Palu City in facing the COVID-19 pandemic? The results of this study reveal that the myths surrounding COVID-19 in Palu City influence people's mentality, to do what is informed by these myths. Erroneous interpretations in the representative mode of messages in myths make the information that reaches the recipient of the message biased. This information bias is exacerbated by the rapid distribution of this message on social media. Massive exposure to social media affects society mentally, without making in-depth interpretations of the messages in the myths conveyed. It is hoped that the results of this research can serve as input for the Palu City Government to seriously educate the public regarding matters related to the COVID-19 pandemic, as input for educational institutions to conduct further research, as learning for the community, and as input for health institutions, to maximize the potential for health promotion, especially in order to combat myths around COVID-19.